Pre-service mathematics teachers' relational understanding in solving special cases of systems of linear equations in two variables - David Pratama; Septiani Yugni Maudy; Warissara Audjam (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to describe the profile of Pre-service Mathematics Teachers' relational understanding in solving special cases of Systems of Linear Equations in Two Variables (SLETV) and to identify the factors underlying the emergence of cognitive impasse during the solving process. Using a qualitative method with a case study approach, the research was conducted on two final-year students at a state university in Karawang through whiteboard observations and unstructured clinical interviews during a comprehensive examination. The findings reveal that while students are proficient in solving routine problems with a single solution, they face a complete standstill when variables are entirely eliminated, such as in 0 = 0 or 0 = c results. Students tend to memorize technical steps without understanding the logical meaning behind the